Empathy and burnout in medical staff: mediating role of job satisfaction and job commitment - Yue, Zongpu; Qin, Yang; Li, Ying; Wang, Jian; Nicholas, Stephen; Maitland, Elizabeth; Liu, Cai (BMC public health, 2022)
Background Burnout is a growing problem among medical staff worldwide and empathy has been described as an essential competence to attenuate burnout. Previous studies found job satisfaction and job commitment were affected by the empathy and associated with burnout. This study explores the effect and mechanism of empathy on burnout on medical staff and investigates the mediating role of job satisfaction and job commitment in the relationship between empathy and burnout among medical staff. Methods Based on a self-administered questionnaire which included the Maslach Burnout Inventory (MBI) to measure burnout, 335 responses from medical staff in Tianjin City, China, yielded data on socio-demographic characteristics, empathy, burnout, job satisfaction and job commitment. Bivariate correlation and structured equation modeling (SEM) analyzed the relationships between empathy, job satisfaction, job commitment and burnout multi-group invariant analysis was used to evaluate whether the model was consistent across different type and level of hospitals and different job and employment type subgroups. Results A total of 202 (60.3%) medical staff had low level burnout, 115 (34.3%) staff had the moderate level and 18 (5.4%) staff had the high level burnout. The results of the SEM showed that empathy not only had a direct negative effect on burnout ( β = - 0.401 , P < 0.001 ) , but also had an indirect impact through job satisfaction ( β = - 0.373 , P < 0.001 ) and job commitment ( β = 0.489 , P < 0.001 ) . Job commitment was negatively associated burnout ( β = - 0.513 , P < 0.001 ) , but, unexpectedly, job satisfaction was positively associated with burnout ( β = 0.177 , P < 0.001 ) . The results also indicated the model was consistent across employment type ( Δ χ 2 = 5.904, p > 0.05) and hospital type ( Δ χ 2 = 7.748, p > 0.05), but was inconsistent across hospital level ( Δ χ 2 = 42.930, p < 0.05) and job type ( Δ χ 2 = 52.912, p < 0.05). Conclusions Our results pointed out the important role that empathy plays in addressing burnout and revealed that managing job satisfaction and increasing the job commitment attenuated burnout. We recommend that the government should accelerate the reform of the resourcing of different hospital levels; facilitate hospital managers to implement additional training; and support hospitals to strengthen psychological testing and counseling to reduce medical staff burnout.